ANALISIS BUDAYA ORANISASI, MOTIVASI DAN KEPUASAN KERJA TERHADAP LOYALITAS DOSEN DAN TENAGA KEPENDIDIKAN (studi kasus di STIE Totalwin semarang) - Dita Ditia Putri; Kiswoyo Kiswoyo; Emi Wardati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this research is to analyze the influence of organizational culture, work motivation, job satisfaction, on loyalty and the simultaneous influence between variables influencing organizational culture, work motivation, job satisfaction, on sampling loyalty from populations determined by saturated sampling (census) and the sample size of 44 respondents.The method used to analyze the data is a regression analysis which previously tested the data first with the reliability test, validity test, normality test and classical statistical assumptions, for this classic assumption test consists of multicollinearity, heteroscedasticity tests.The results obtained show that organizational culture, work motivation, job satisfaction positive and significant effect on loyalty